1999
DOI: 10.1111/j.1530-0277.1999.tb04074.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on Leptin Secretion and the Leptin‐Induced Luteinizing Hormone (LH) Release From Late Juvenile Female Rats

Abstract: These data demonstrate that EtOH administration not only can suppress peripheral levels of leptin, but also blocks its central action to facilitate LH secretion. Although replacement of leptin can reverse the EtOH-induced suppression of LH by a direct action at the level of the pituitary, it cannot elevate serum IGF-1; a peripheral signal that acts centrally to stimulate LH releasing-hormone (LHRH)/LH release during the juvenile-peripubertal transition period, and thus accelerates the initiation of female pube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Nevertheless, in our rats, serum leptin did not significantly correlate with serum LH. Hiney et al reported that leptin replacement was able to reverse the suppressed levels of LH caused by ethanol, but the onset of puberty was still delayed [24]. These results buttress our findings that LH is not the sole hormone which initiates puberty [25, 26].…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, in our rats, serum leptin did not significantly correlate with serum LH. Hiney et al reported that leptin replacement was able to reverse the suppressed levels of LH caused by ethanol, but the onset of puberty was still delayed [24]. These results buttress our findings that LH is not the sole hormone which initiates puberty [25, 26].…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, in our rats, serum leptin did not significantly correlate with serum LH. Hiney et al reported that leptin replacement was able to reverse the suppressed levels of LH caused by ethanol, but the onset of puberty was still delayed [ 24 ]. These results buttress our findings that LH is not the sole hormone which initiates puberty [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In female rats, chronic exposure to ethanol early in adolescence alters serum concentrations of hormones associated with puberty, such as luteinizing hormone, 95 and delays puberty. 96,97 In contrast, chronic exposure to alcohol beginning before and continuing through adolescence has been reported to increase aggressive behavior and testosterone levels in male hamsters 98 and to advance the onset of sexual behavior in male rats, 99 although delays in puberty-related increases in testosterone levels and sex organ size after adolescent alcohol exposure in male rats have also been reported. 100 …”
Section: Developmentally Related Effects Of Alcohol Use and Exposurementioning
confidence: 99%